Pengukuran Kualitas Layanan Sistem Informasi Akademik dengan Metode WebQual 4.0, Customer Satisfaction Index (CSI) dan Importance Performance Analysis (IPA) Terpadu - Kurniawan Eko Saputro (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The Academic Information System (SIAKAD) of Tadulako University is an academic portal in the form of a web application that has an important role in the academic activities of stakeholders, especially students and lecturers of Tadulako University. However, during its implementation, SIAKAD has never been measured on the quality of its services and overall user satisfaction from various aspects and user perspectives, so that developers and universities as SIAKAD organizers do not yet know the feedback from users as a reference for the success rate of SIAKAD. This study aims to measure the quality of SIAKAD services from the user's perspective. This research instrument uses the WebQual 4.0 method which consists of the variables of Quality of Use, Quality of Information, and Quality of Service Interaction. The data analysis used consists of the Customer Satisfaction Index (CSI) method which is used to measure the overall level of service user satisfaction and Importance Performance Analysis (IPA) which plays a role in mapping service attributes/indicators into the IPA quadrant so that attributes that need to be improved and maintained will be obtained. . The results of the analysis show that the value of the gap on all attributes in all variables is negative. This shows that the respondent's expectation value for all attributes is higher than the reality value. Based on the CSI calculation, the result is 73,391. This value is in the range of 66% - 80.99%. This means that users are satisfied with the performance of information system services. The results of the Cartesian diagram mapping show that indicators of service implementation, actual information, good reputation, and transaction security should be a major concern for the university because these indicators have high user expectations but low reality/performance values.